The Effect of Ajwa Date (Phoenix dactylifera) Extract on the Histopathology of Pancreatic Islets in Mice with Diabetes Mellitus - Arna, Nadhifa; Humairah, Ira; Susanto, Joni; Yuliawati, Tri Hartini (Universitas Airlangga, 2024)
Introduction: It is necessary to develop alternative antidiabetic therapies that are safer and more affordable to overcome the high prevalence of diabetes mellitus in Indonesia. Ajwa dates (Phoenix dactylifera) have a high flavonoid content; hence, this study aimed to investigate their effect on streptozotocin-induced diabetes mellitus mice by examining the number of beta cells and the islets of Langerhans. Methods: Twenty-five mice were divided into five groups: a negative control group (K1), a positive control group (K2), and three treatment groups (P1, P2, and P3). The K2, P1, P2, and P3 groups were induced by 100 mg/kg bw of streptozotocin. Additionally, the P1, P2, and P3 groups received oral treatment using ajwa date methanol extract at different doses of 3, 5, and 7 g/kg bw, respectively. The treatment was administered daily for four weeks. The initial analysis included the homogeneity test and the Shapiro-Wilk test. As the data were non-normally distributed, the analysis proceeded with the Kruskal-Wallis test (p<0.05). Results: The comparative analysis revealed significant differences in the number of beta cells among the groups, with a notable decrease observed in the K2 group and an increase in each treatment group. The measurement of the islets of Langerhans exhibited significant differences among the groups, with p=0.001. Conclusion: The administration of ajwa date methanol extract can affect the number of beta cells and the islets of Langerhans in mice with diabetes mellitus. Highlights: 1. This original study examined the antioxidant compounds derived from naturally sourced ajwa date (Phoenix dactylifera) extract. 2. Ajwa date extract has the potential to protect against histological damage, specifically to beta cells and pancreatic islets, in mice induced by streptozotocin.